(untitled) (Journal of Plant Disease Sciences, 2018)
Tomato (Solanum lycopersicum L.) is the most important solanaceous vegetable crop grown in the mid hills of Himachal Pradesh. Worldwide production of tomato is estimated as 163 million tonnes over an area of 4.8 million ha (Anonymous, 2015). India is second largest producer of tomato after China with annual production of 18.73 million tonnes from an area of 0.88 million ha (Anonymous, 2015). In Himachal Pradesh , it is cultivated over an area of 10,400 ha with annual production of 430.79 thousand tonnes. Solan district is leading with annual production of 232 thousand tonnes over an area of 4640 ha (Anonymous, 2015).